2015
DOI: 10.1002/ccd.26378
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, treatment, and outcome of acute aortic valve regurgitation complicating percutaneous balloon aortic valvuloplasty

Abstract: AAR is a fearsome complication of BAV and portends a grim prognosis. In some cases, it can be resolved with appropriate technical maneuvers; in others, a rescue TAVI or surgical valve replacement may be necessary. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…We would like to highlight that the study protocol mandated balloon inflation at a nominal pressure, so as not to determine any bias between the groups. At our institute, BAV was usually performed without RP, allowing the operator to adapt inflation pressure upon aortic valve sealing, at times even over‐expanding the balloon . The predefined less aggressive approach adopted in this trial might have influenced the final efficacy outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to highlight that the study protocol mandated balloon inflation at a nominal pressure, so as not to determine any bias between the groups. At our institute, BAV was usually performed without RP, allowing the operator to adapt inflation pressure upon aortic valve sealing, at times even over‐expanding the balloon . The predefined less aggressive approach adopted in this trial might have influenced the final efficacy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, for safety reasons, the operator is discouraged from upgrading balloon size even in the presence of a suboptimal procedural result. When rapid pacing is applied, the pressure curve is abolished due to deliberately ineffective contractions and so the operator cannot rely on the sealing concept (Figure B) …”
Section: Methodsmentioning
confidence: 99%
“…7,8,12-14 For example, a previous study reported a 1.7% incidence rate of acute AR, with 50% of this incidence occurring just after the first inflation of the balloon. 21, 23 We speculate that our protocol of gradual upsizing of the balloon by inflation under biplane-TEE monitoring contributed to avoiding acute AR caused by a forced excessive valve dilatation, as well as avoiding rupture of the annulus by an excessively oversized balloon. 5,7, 24 Moreover, the antegrade approach has the potential to injure the mitral valve apparatus, which results in acute MR; the Brockenbrough procedure for the transseptal approach has a risk of cardiac tamponade.…”
Section: Discussionmentioning
confidence: 88%
“…In the majority of cases, acute AR is caused by either infective endocarditis of the aortic valve or an aortic dissection. 1,2 In rare cases, acute AR is caused by a traumatic rupture of valve leaflets, 3 due to complications of procedures such as aortic balloon valvotomy 4 or rupture of fenestrated cusps. 5 A few cases of AR in the presence of fibrous strands have been reported.…”
Section: Discussionmentioning
confidence: 99%